Factors limiting fast bowling performance in cricket - Paul Felton (2014)
In cricket, fast bowlers utilise the speed at which they are able to deliver the ball in order to be successful. Previous research has investigated the effect of different technique parameters on ball release speed using an experimental approach. While an experimental approach is suitable to understand the differences between bowlers it is not suitable to understand the changes required to improve a bowler’s performance. The aim of this research was to investigate the factors that limit fast bowling using a theoretical approach. A 16-segment subject-specific torque-driven computer simulation model of the front foot contact phase of fast bowling was developed, with wobbling masses included within the shank, thigh and torso representations. Torque generators were included at the MTP, ankle and knee joints on the front leg, both hip and shoulder joints, and the elbow and wrist joints on the bowling arm. [Continues.]